PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS POE PREDICT OBSERVE EXPLAIN PADA MATERI SISTEM PENCERNAAN DAN PERNAPASAN PADA MANUSIA DI KELAS XI SMA - Supriyanto Tri Andi Ama; Mistianah Mistianah (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2018)
This study aims to: (1) develop Student Worksheets (LKS) based on the Predict Observe Explain Model for Class XI High School and (2) find out the feasibility test of Student Worksheets (LKS) based on the Predict Observe Explain model on the digestive system and respiratory system material in human. This research is a type of development research (research and development) with the 4D model (Define, Design, Develop, and Disseminate). This research was conducted in March 2018 until July 2018 at IKIP BUDI UTOMO Malang. Data analysis techniques were carried out using descriptive analysis with feasibility tests from material experts and media experts. The results of this study are: (1) the development of Student Worksheets (LKS) based on the Predict Observe Explain (POE) model produces a pre-filled section containing the main title page, preface, table of contents, competency map and instructions for use, the contents of the digestive system material and the human respiratory system and practice questions, the post-contents section contains a bibliography and author's profile with a total of 62 pages using 70 grams of HVS paper to fill the LKS and AP 120 paper for the cover of the LKS, printed with A5 paper size. (2) the results of the feasibility assessment by material experts get an average number of scores of 41.5 with a mean score of 3.4 which includes eligible criteria. Feasibility assessment of media experts get an average score of 43 with a mean score of 3.3 which includes Eligible criteria so that LKS based on the Explain Predict Observe model is suitable for use as teaching material